2005
DOI: 10.1093/alcalc/agh182
|View full text |Cite
|
Sign up to set email alerts
|

Intention to Change Drinking Behaviour in General Practice Patients With Problematic Drinking and Comorbid Depression or Anxiety

Abstract: Individuals with problematic drinking and comorbid anxiety or depression may be well accessible for pro-active intervention to reduce drinking. Strategies should focus on the enhancement of coping skills to control temptation and self-efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 27 publications
3
15
0
2
Order By: Relevance
“…This finding may be of importance as has been demonstrated that once the problematic alcohol use can be detected and modified at an earlier stage, then alcohol related problems can be prevented [36,37]. …”
Section: Discussionmentioning
confidence: 99%
“…This finding may be of importance as has been demonstrated that once the problematic alcohol use can be detected and modified at an earlier stage, then alcohol related problems can be prevented [36,37]. …”
Section: Discussionmentioning
confidence: 99%
“…1 Considering the final inclusion criteria. 2 Inappropriate age range was determined in the initial contact via phone prior to the execution of the screening procedure. 3 After explaining the study on the phone and/or sending out the study information via E-mail or postal letter.…”
Section: Interventionmentioning
confidence: 99%
“…However, their impact might be diminished by the concurrent existence of mental health problems. Numerous studies have shown that mental health problems are associated with cognitive and motivational patterns that could hinder individuals from successfully changing substance use behavior [2][3][4]. Thus, in individuals with comorbid mental disorders, single-focused interventions targeting alcohol consumption might not be sufficient to change consumption patterns.…”
Section: Introductionmentioning
confidence: 99%
“…Although previous studies have implicated POCs in successful behavior change for alcohol abuse (Ferguson, 1998;Santos Diez et al, 2001;Snow et al, 1994; also see Carbonari & DiClemente, 2000;Freyer et al, 2006;Grothues et al, 2005;Hodgins et al, 1997;Isenhart & Van Krevelan, 1998;Migneault et al, 2005), there has been uncertainty regarding strategy preferences, across and within AUD groups. Thus, on the one hand existing literature suggests strategies for managing high-risk situations, notably stimulus control, facilitate behavior change in people with addiction to alcohol (Bien et al, 1993;Snow et al, 1994).…”
Section: Researchmentioning
confidence: 99%
“…Studies have found POCs useful in motivating behavior change in people with AUDs (Ferguson, 1998;Snow, Prochaska, & Rossi, 1994). For example, Snow et al (1994) found action-oriented POCs such as stimulus control and reinforcement management useful in eliciting behavior change in people with an alcohol dependency (also see Carbonari & DiClemente, 2000;Freyer et al, 2006;Grothues et al, 2005;Hodgins, Ungar, el-Guebaly, & Armstrong, 1997;Isenhart & Van Krevelan, 1998;Migneault et al, 2005). However, there is a paucity of literature on utilization differentials between and within AUD groups.…”
Section: Introduction Disordersmentioning
confidence: 99%